If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2k + 1 = 7 + 5k + -4k Reorder the terms: 1 + 2k = 7 + 5k + -4k Combine like terms: 5k + -4k = 1k 1 + 2k = 7 + 1k Solving 1 + 2k = 7 + 1k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-1k' to each side of the equation. 1 + 2k + -1k = 7 + 1k + -1k Combine like terms: 2k + -1k = 1k 1 + 1k = 7 + 1k + -1k Combine like terms: 1k + -1k = 0 1 + 1k = 7 + 0 1 + 1k = 7 Add '-1' to each side of the equation. 1 + -1 + 1k = 7 + -1 Combine like terms: 1 + -1 = 0 0 + 1k = 7 + -1 1k = 7 + -1 Combine like terms: 7 + -1 = 6 1k = 6 Divide each side by '1'. k = 6 Simplifying k = 6
| 9x+35=5x-19 | | 5(8+3x)=100 | | (-6x^2+7x-6)-(8x^2+3x-9)+(7x^2-7x+8)= | | 2x*15=45 | | 2xy-15=45 | | 5(3x-2)=80 | | 2x+20y+11+5x-11y-9= | | 5(-7x-4)=-265 | | E=245c^2 | | 6-2v-4v=-15-3v | | 3x+2y=45 | | -9a=27 | | 5(-9+2x)=-155 | | (2x+9)+(4x-15)=90 | | -3x^2+9x+120=0 | | 7(2+3x)=-91 | | 1-3m=-5-m-4m | | 8x^2-5x+2.5=0 | | -7(2-2x)=-14 | | x+10-7x=12-6x-2 | | b/9-12=18 | | 8d-6d-8=2d | | -7(8-6x)=-56 | | 0.2(6x-3)=0.4(x-2)+0.2 | | (2b+c)(3b+2c)=0 | | X+x^2/2+2x^2-x | | -x+20=-2x-25 | | -3(-7x+5)=153 | | 9=6+2(x+1) | | 30=5(x*5)*2 | | N+8=-11+n+5+2n | | 10x+14=8x+9 |